Casuistic Use of High-Dose Methylprednisolone in a Child with Acute Encephalopathy due to Metabolic Crisis in HIBCH Deficiency - Ida Bo Nissen; Johnny Kent Christensen; Allan Meldgaard Lund; Line Caroe Sorensen (Journal of Inborn Errors of Metabolism and Screening)
Abstract 3-hydroxyisobutyryl-CoA hydrolase deficiency (HIBCHD) is a rare metabolic disease. Early symptoms include poor feeding, seizures, hypotonia and impaired psychomotor development. Acute metabolic crisis can cause encephalopathy with high risk of neurological sequelae or death. Casuistic, we here report a nine-year old Danish girl with HIBCHD treated with intravenous high-dose methylprednisolone when presenting with encephalopathy during acute metabolic crisis. Presentation of acute encephalopathy with basal ganglia changes seen on MRI was regarded as acute disseminated encephalomyelitis (ADEM) leading to intravenous high-dose methylprednisolone treatment. The effect of methylprednisolone was profound, not only on the acute neurological symptoms, but also accelerated the development of the child. After re-evaluation of MR images, Whole Genome Sequencing (WGS) confirmed the diagnosis HIBCHD. The high-dose methylprednisolone treatment regime was repeated in a following severe metabolic crisis presenting with acute encephalopathy, dystonia and spasticity. The child survived and after rehabilitation neurological sequelae are present but considerably reduced. We consider if high-dose methylprednisolone should be recommended in children with acute metabolic crisis and encephalopathy due to HIBCHD. Since influenza A virus was the triggering cause to metabolic crisis with encephalopathy, vaccination should be considered in HIBCHD.